2022
DOI: 10.1038/s41388-022-02283-0
|View full text |Cite
|
Sign up to set email alerts
|

H3K9me3 represses G6PD expression to suppress the pentose phosphate pathway and ROS production to promote human mesothelioma growth

Abstract: The role of glucose-6-phosphate dehydrogenase (G6PD) in human cancer is incompletely understood. In a metabolite screening, we observed that inhibition of H3K9 methylation suppressed aerobic glycolysis and enhances the PPP in human mesothelioma cells. Genome-wide screening identified G6PD as an H3K9me3 target gene whose expression is correlated with increased tumor cell apoptosis. Inhibition of aerobic glycolysis enzyme LDHA and G6PD had no significant effects on tumor cell survival. Ablation of G6PD had no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Our work demonstrated PFKFB3 is a novel substrate of Aurora-A, and a major determinant for Aurora-A-induced cancer progression. To our knowledge, our study uncovered a novel mechanism of Aurora-A as an oncogene to promote tumor cell glycolysis and The advantages of accelerated glycolytic flux in tumors remain controversial [30,31]. Our data suggested that PFKFB3-regulated glycolysis can promote the proliferation and invasion of TC cells by enhancing the energy supply, an important mechanism of Aurora-Amediated TC cell progression.…”
Section: Discussionmentioning
confidence: 73%
“…Our work demonstrated PFKFB3 is a novel substrate of Aurora-A, and a major determinant for Aurora-A-induced cancer progression. To our knowledge, our study uncovered a novel mechanism of Aurora-A as an oncogene to promote tumor cell glycolysis and The advantages of accelerated glycolytic flux in tumors remain controversial [30,31]. Our data suggested that PFKFB3-regulated glycolysis can promote the proliferation and invasion of TC cells by enhancing the energy supply, an important mechanism of Aurora-Amediated TC cell progression.…”
Section: Discussionmentioning
confidence: 73%
“…The advantages of accelerated glycolytic ux in tumors remain controversial (29,30). Our data suggested that PFKFB3-regulated glycolysis can promote the proliferation and invasion of TC cells by enhancing the energy supply, an important mechanism of Aurora-A-mediated TC cell progression.…”
Section: Discussionmentioning
confidence: 74%
“…The present finding showed that gluconolactone was upregulated in the DCI group. The upregulation was possible because glucose has 2 parallel and competing metabolic pathways: the glycolytic and the pentose phosphate pathways 23 . Therefore, the reduction of oxoglutaric acid of glycolysis in this study may increase gluconolactone in the pentose phosphate pathway.…”
Section: Discussionmentioning
confidence: 99%